Trancendental Meditation Control Blood Sugar Levels On Elderly People - Damayanti, Santi; Sucipta, I Kadek Indra; Erwanto, Rizky (Universitas Islam Lamongan, 2020)
The proportion of diabetes melitus patientâ€™s number increases along with age. The proportion of glucose tolerance disorder increases along with age among people in the 65-74 age group. The transcendental meditation therapy is a therapyÂ to lower the cortisone hormone level, in order to increase the effectiveness of the insulin hormone. Objective to determine the effectiveness of transcendental meditation therapy on blood glucose level in elderly people. Methods research is a quasi experiment research with a pre and post test without control design, the research sample were selected using a consecutive sampling technique, as much as 31 respondents. The data collected were analyzed using Wilcoxon test. Result of statistic test before the meditation therapy showed a minimum value of 104 and maximum value of 420 with a median value of 179.00, and after the meditation therapy, the result showed minimum value of 85 and maximum value of 282 with a median value of 129.00. Result of the statistic test using Wilcoxon test showed a p-value =0.000(p-value<0.05) Conclusion is an influence of transcendental meditation therapy on blood glucose level in elderly people at BPSTW Yogyakarta Budi Luhur Unit, Kasihan Bantul.